Exploring the Potential of Indonesia's Documentary Film Genre on OTT - Ramli, Arwin; Nehe, Berita Mambarasi; Kremer, Hendri (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Indonesia's documentary filmmaking industry was undergoing a transformative phase, driven by a resurgence of public interest and the expanding reach of Over-the-Top (OTT) platforms. This study explored the potential of Indonesian documentaries to thrive in the OTT ecosystem, considering the industry's recent growth, including the production of 168 films in 2020, and increasing international recognition. The success of platforms such as Australia's iWonder underscored the viability of dedicated streaming services for documentary content, presenting a model that could inspire similar initiatives in Indonesia. This research highlighted the convergence of the growing demand for authentic, culturally rich narratives and the accessibility offered by OTT platforms. It analyzed the opportunities for Indonesian filmmakers to expand their audience reach, both domestically and globally, by leveraging these platforms. Furthermore, the study identified the potential for specialized documentary platforms to foster a community of viewers enthusiastic about real-life narratives and societal issues. The findings emphasized the need for continued research to understand audience preferences and support the development of innovative distribution models for Indonesian documentaries on OTT platforms. By capitalizing on the rapid growth of digital streaming and public interest in documentaries, Indonesia could enhance the visibility and impact of its documentary genre, contributing to cultural enrichment, education, and meaningful societal discourse.